Activated α2-Macroglobulin regulates LRP1 levels at the plasma membrane through the activation of a Rab10-dependent exocytic pathway in retinal Müller glial cells - Jaldín Fincati, Javier Roberto (2019)
Activated α2-macroglobulin (α2M*) and its receptor, low-density lipoprotein receptor-related protein 1 (LRP1), have been linked to proliferative retinal diseases. In Müller glial cells (MGCs), the α2M*/LRP1 interaction induces cell signaling, cell migration, and extracellular matrix remodeling, processes closely associated with proliferative disorders. However, the mechanism whereby α2M* and LRP1 participate in the aforementioned pathologies remains incompletely elucidated. Here, we investigate whether α2M* regulates both the intracellular distribution and sorting of LRP1 to the plasma membrane (PM) and how this regulation is involved in the cell migration of MGCs. Using a human Müller glial-derived cell line, MIO-M1, we demonstrate that the α2M*/LRP1 complex is internalized and rapidly reaches early endosomes. Afterward, α2M* is routed to degradative compartments, while LRP1 is accumulated at the PM through a Rab10-dependent exocytic pathway regulated by PI3K/Akt. Interestingly, Rab10 knockdown reduces both LRP1 accumulation at the PM and cell migration of MIO-M1 cells induced by α2M*. Given the importance of MGCs in the maintenance of retinal homeostasis, unravelling this molecular mechanism can potentially provide new therapeutic targets for the treatment of proliferative retinopathies.